2016
DOI: 10.1016/j.bbalip.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

CD36 actions in the heart: Lipids, calcium, inflammation, repair and more?

Abstract: CD36 is a multifunctional immuno-metabolic receptor with many ligands. One of its physiological functions in the heart is the high-affinity uptake of long-chain fatty acids (FAs) from albumin and triglyceride rich lipoproteins. CD36 deletion markedly reduces myocardial FA uptake in rodents and humans. The protein is expressed on endothelial cells and cardiomyocytes and at both sites is likely to contribute to FA uptake by the myocardium. CD36 also transduces intracellular signaling events that influence how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 96 publications
2
64
0
1
Order By: Relevance
“…The role of GPR40 and CD36 in the upregulation of proinflammatory cytokine expression was further supported by our findings that inhibition of GPR40 or CD36 attenuated proinflammatory cytokine expression in gingival fibroblasts stimulated by palmitate and LPS (Figure ). Consistently, studies from other laboratories have also demonstrated a vital role of free fatty acid receptors GPR40 and CD36 in SFA‐promoted inflammation …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The role of GPR40 and CD36 in the upregulation of proinflammatory cytokine expression was further supported by our findings that inhibition of GPR40 or CD36 attenuated proinflammatory cytokine expression in gingival fibroblasts stimulated by palmitate and LPS (Figure ). Consistently, studies from other laboratories have also demonstrated a vital role of free fatty acid receptors GPR40 and CD36 in SFA‐promoted inflammation …”
Section: Discussionsupporting
confidence: 79%
“…Consistently, studies from other laboratories have also demonstrated a vital role of free fatty acid receptors GPR40 and CD36 in SFA-promoted inflammation. 31,32 Regulation of surface receptor expression is a well-known cell function to control cellular response to ligands or uptake of ligands. 33,34 Under certain conditions, cells either upregulate or downregulate the receptor expression, resulting in increased or decreased cell response to ligands and ligand uptake, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged fasting has recently been suggested to be involved in intestinal inflammation because of reduced serum antioxidant levels (Abdeen, Mathew, Khan, Dashti, & Asfar, ) and increased immunoglobulin (Lara‐Padilla et al., ) in humans. Cluster differentiation (CD‐36) has been involved in fatty acid transportation (Kitessa et al., ), although recently it has been associated with binding with a pro‐inflammatory cytokine, TLR‐4 (toll‐like receptor‐4) (Abumrad & Goldberg, ). Toll‐like receptors ‐4 binds with the bacterial toxins and has been involved in gut inflammation (Andrade et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The TGs in CM particles are hydrolyzed by LPL in adipose, skeletal muscle, and heart vascular beds to deliver FFAs for cellular uptake facilitated by membrane cluster of differentiation 36 (CD36) (3). These tissues quantitatively contribute to CM clearance in humans (4)(5)(6) and express high levels of CD36 at the level of both endothelial and parenchymal cells (7,8). Elevated concentrations of postprandial CM remnants after an oral fat load were reported in four subjects with complete CD36 deficiency (9), suggesting that low CD36 might impair CM clearance and result in sustained high levels of circulating CM remnants (10,11).…”
Section: Metabolic Phenotype Transcript Level Dna Methylation and mentioning
confidence: 99%